Debt crisis and 10-year sovereign yields in Ireland and in Portugal - Afonso, António (2017)
We assess the determinants of the 10-year sovereign yield for the period 2000-2015, in Portugal and in Ireland. Results show that the long-term Portuguese sovereign yield increased with the rise of the 10-year Bund yield and during the Securities Markets Programme, but decreased due to financial integration. Additionally, during the period of the economic and financial adjustment programme, there was evidence of additional rises (decreases) due to increases (decreases) in the 3-month Euribor rate, and the level of public debt. EU/IMF funding reduced sovereign yield.